Corn-like, recoverable γ-Fe2O3@SiO2@TiO2 photocatalyst induced by magnetic dipole interactions - Fang Wang (Nature Portfolio, 2017)
Abstract Corn-like, γ-Fe2O3@SiO2@TiO2 core/shell heterostructures were synthesized by a modified solvothermal reduction combined with a sol-gel method. SiO2 shells were first deposited on monodisperse Fe3O4 microspheres by a sol-gel method. Fe3O4@SiO2@TiO2 corn-like heterostructures were then obtained by sequential TiO2 coating, during which the magnetic dipolar interactions induced the anisotropic self-assembly process. After annealing at 350 °C, the crystalized TiO2 enhanced photocatalytic activity, while Fe3O4 was converted to γ-Fe2O3. The corn-like γ-Fe2O3@SiO2@TiO2 photocatalyst can be recycled and reused by magnet extraction. Despite the photocatalytic activity decreased with each cycle, it can be completely recovered by moderate heating at 200 °C.